PERENCANAAN KAWASAN EKO-WISATA TAMAN ASTOR, KABUPATEN BOGOR - Steven Joe; Suryono Herlambang; I.G. Oka Sindhu Pribadi (Jurusan Arsitektur dan Perencanaan, 2020)
AbstrackPerum Perhutani, is a State-Owned Enterprise in charge of managing forest areas for the benefit of preservation and public benefit. Within the Perhutani management area, many areas also function as tourist areas. One of them is the Taman Astor tourist area in Tenjo District, Bogor Regency, which is currently under the management of Perum Perhutani KPH Bogor. Even though it has high tourism potential, Taman Astor still has few visitors. This is due to the concept of a tourist park that is less focused and the supporting facilities provided in the area are limited. To improve the quality of the area and the quantity of visitors, this study is carried out in various stages of the planning process: starting with a comparative study and SWOT analysis, followed by a series of technical analyzes, such as: site and place analysis, analysis of tourist attractions, analysis of best practice (case study) , space requirements analysis, to produce the Taman Astor Tourism Development Concept with the Ecotourism concept. This concept emphasizes, in addition to adding natural and recreational tourism attractions, it also pays attention to the principles of forest conservation and the involvement of the surrounding community in the use and management of the area. Keywords: land use of Perum Perhutani, the concept of eco-tourism, nature recreation, forest preservation atau conservation, involvement of the surrounding communityAbstrakPerum Perhutani, adalah Badan Usaha Milik Negara (BUMN) yang bertugas mengelola area hutan untuk kepentingan pelestarian dan kemanfaatan umum. Dalam wilayah pengelolaan Perhutani, banyak area yang juga berfungsi sebagai kawasan wisata. Salah satu adalah kawasan wisata Taman Astor yang berada di Kecamatan Tenjo, Kabupaten Bogor, yang saat ini di bawah pengelolaan Perum Perhutani KPH Bogor. Meskipun memiliki potensi wisata yang tinggi, Taman Astor masih sedikit pengunjungnya. Hal ini disebabkan konsep taman wisata yang kurang terarah dan terbatasnya fasilitas penunjang yang disediakan di area tersebut. Untuk meningkatkan kualitas kawasan dan kuantitas pengunjung, studi ini dilakukan dengan berbagai tahapan proses perencanaan: diawali dengan studi komparasi dan analisis SWOT, dilanjutkan dengan rangkaian analisis teknis, seperti: analisis lokasi dan tapak, analisis daya tarik wisata, analisis best practice (studi kasus), analisis kebutuhan ruang, untuk menghasilkan Konsep Pengembangan Wisata Taman Astor dengan konsep Ekowisata. Konsep ini menekankan, selain penambahan atraksi wisata alam dan rekreasi juga memperhatikan prinsip-prinsip konservasi hutan dan pelibatan masyarakat sekitar dalam pemanfaatan dan pengelolaan kawasan.